2020
DOI: 10.1111/jsr.13231
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of sleep changes during the COVID‐19 pandemic: Demographic, behavioural and psychological factors

Abstract: Summary This study aimed to evaluate changes in sleep during the COVID‐19 outbreak, and used data‐driven approaches to identify distinct profiles of changes in sleep‐related behaviours. Demographic, behavioural and psychological factors associated with sleep changes were also investigated. An online population survey assessing sleep and mental health was distributed between 3 April and 24 June 2020. Retrospective questions were used to estimate temporal changes from before to during the outbreak. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 41 publications
14
137
3
4
Order By: Relevance
“…In younger children the main interventions should be related to the sleep health education through parents, cognitive behavioral therapy for insomnia and interventions related to a treatment of a possible post-traumatic stress disorders, as indicated by the increase of anxiety at bedtime and nightmares. In older children and adolescents, cognitive behavioral therapy for insomnia and chronobiotic therapies for delayed bedtimes (e.g., morning light therapy and exogenous melatonin intake about 2 hours before habitual sleep time) should be implemented[ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In younger children the main interventions should be related to the sleep health education through parents, cognitive behavioral therapy for insomnia and interventions related to a treatment of a possible post-traumatic stress disorders, as indicated by the increase of anxiety at bedtime and nightmares. In older children and adolescents, cognitive behavioral therapy for insomnia and chronobiotic therapies for delayed bedtimes (e.g., morning light therapy and exogenous melatonin intake about 2 hours before habitual sleep time) should be implemented[ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of new sleep difficulties during the confinement was associated with female sex, being employed and family responsibilities, among other factors [ 25 ]. We found that the improvement of sleep quality observed after the end of the confinement was more frequent in female and in working-age people than in the rest of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Worse sleep quality with confinement has been reported among the adult general population in different countries (11)(12)(13)65), and partly attributed to inactivity (12) and higher anxiety and mental distress during isolation (21). In our study, the association with mental health during quarantine was confirmed, with an increased risk of reducing sleep quality in individuals with higher GDS-10 scores (RRR: 1.25; 95%CI: 1.13-1.39; data not shown in tables).…”
Section: What Do Other Studies Say About Changes In Sleep Duration Anmentioning
confidence: 99%
“…A few studies have investigated the health consequences of the lockdown during the first wave of the pandemic in the Spanish adult population. Using convenience sample surveys conducted between March and June 2020, in which participants reported their perceived changes in lifestyle and health-related factors since the start of the pandemic, these studies have shown a general worsening in psychological and mental health (8–10), as well as in sleep quality (1113), mild or no changes in tobacco and alcohol consumption (11,14), slight or no changes in weight (1416), conflicting results for diet quality (17,18), important reductions in physical activity and increases in sedentary time (11,1921). Interestingly, one survey found that the percentage of interviewees meeting the guidelines regarding screen time became lower between March 22 nd and April 5 th , while unhealthy alcohol consumption and insufficient physical activity decreased during this three-week period (22).…”
Section: Introductionmentioning
confidence: 99%